2019
DOI: 10.1097/md.0000000000015011
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of proton pump inhibitors increase the risk of hypomagnesemia

Abstract: Background: Proton pump inhibitors (PPIs) are commonly used in the treatment of acid-related diseases; however, the association between the use of PPIs and potential risk of hypomagnesemia is controversial. Methods: In the present study, databases including PubMed, EMBASE, MEDLINE, PsycINFO, CINAHL, the Cochrane Library, and 4 Chinese databases were searched since the inception until April 2018. Previous observational studies on the incidence of hypomagnesemia in indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
0
24
1
1
Order By: Relevance
“…Many studies have suggested an increased risk and that hypomagnesemia develops in a proportion of PPI users [131]. Meta-analyses have been problematic due to study heterogeneity, but a recent analysis found that PPI users had an increased risk of hypomagnesemia (RR 1.44) compared to non-users [132], whereas analysis of only high-quality studies found an RR of 1.63 [133]. Hypomagnesemia is rare and it seems that mainly patients who already use a diuretic are at risk [131].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have suggested an increased risk and that hypomagnesemia develops in a proportion of PPI users [131]. Meta-analyses have been problematic due to study heterogeneity, but a recent analysis found that PPI users had an increased risk of hypomagnesemia (RR 1.44) compared to non-users [132], whereas analysis of only high-quality studies found an RR of 1.63 [133]. Hypomagnesemia is rare and it seems that mainly patients who already use a diuretic are at risk [131].…”
Section: Resultsmentioning
confidence: 99%
“…While the aim of this study was not to evaluate the clinical safety of pantoprazole in calves, the lack of observed adverse effects correlate with previously reported pantoprazole use in ruminants for case management of cattle (4,26), camels (27), sheep (15,28), yaks (29), and goats (30,31). Adverse effects of pantoprazole administration described people include hyponatremia (32), hypomagnesemia (33), as well as nephritis and hepatotoxicity (34). Additional adverse effects described in people from proton pump inhibitor administration include thrombocytopenia (35) and neutropenia (36).…”
Section: Discussionmentioning
confidence: 99%
“…When used in humans for therapy, multiple adverse events have been reported from patients administered PPIs, mainly skin reactions, nephritis, pancytopenia, anaphylaxis, edema, hepatotoxicity, as well as biochemical changes such as hyponatremia and hypomagnesemia (8)(9)(10)(11)(12)(13)(14). Pantoprazole specifically has been associated with thrombocytopenia, hepatotoxicity, and pancreatitis (9,11,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%